Assessing Romanian Students’ Digital Skills Based on The Scores at The Baccalaureate Exam - Andreea MIRICA; Octavian CEBAN; Ionela-Roxana PETCU (Communications of International Proceedings, 2022)
Digital skills are not only a major priority but they may become mandatory for an increasing list of jobs in the modern economy facing an increase in automation and extensive inclusion of industrial robotization. Although the IT sector is structurally important in Romania, there is still room for improvements and more to be done to catch-up in terms of advanced and above basic digital skills. Having this highlighted, this research paper aims to analyse the level of digital competences of Romanian youth based on the score registered at the Baccalaureate exam in 2020-2022. Furthermore, we examine to what extent the score in digital competences differ based on demographic characteristics and if it is correlated with the score in other exam components and final average. The source of the data is the Ministry of Education through its open-data portal. The results performed on the score in digital competences by sex and area of residency show significant differences: female candidates score higher compared to their male counterparts and rural students have significantly lower scores in digital competences compared to those living in urban areas. Moreover, the results show medium correlation with significant coefficients between the score in digital competences and scores in other exam subjects.
Keywords: Romania; education system; digital competences; Baccalaureate exam; t-tests